Coagulation Testing Gone Awry; Effect of Direct Oral Anticoagulant (DOAC) Removal on Lupus Anticoagulant Assays. (28th October 2020) - Casa, Daniel; Gil, Morayma Reyes
Abstract: Background: Direct oral anticoagulants (DOACs) such as apixaban and rivaroxaban are widely used to treat those with or at risk for thromboembolic disease. However, DOACs have been shown to interfere with coagulation assays making their interpretations challenging. Importantly, lupus anticoagulant (LA) assays using the dilute Russell Viper Venom Time (dRVVT) to screen for patients at increased risk of thrombosis are particularly affected by DOACs leading to inaccurate results. DOAC removal agents are available to improve dRVVT specificity for LA and eliminate assay interferences. Aims: To evaluate the performance of DOAC-Remove to accurately measure LA in patient plasma. Methods: 10 LA positive and 10 LA negative samples without DOAC as well as normal pool plasma (NPP) were used as controls. We assessed 64 patient plasma samples including 39 patients on apixaban and 25 patients on rivaroxaban (anticoagulation was confirmed by chart review). LA testing by dRVVT was performed using Staclot® DRVV Screen and Staclot® DRVV Confirm reagents on STA R Max analyzer. DRVVT testing was performed before and after DOAC removal (DOAC-Remove, Aniara). DOAC plasma concentrations were measured using STA Liquid Anti-Xa assay. Acceptable DOAC removal was defined as an anti Xa level <0.03 IU/mL. Positive LA was defined as a screen ratio and mix ratio greater than 1.15. Results: Positive and negative samples without DOAC remained the same after DOAC removal treatment. Factor levels in NPP were not affected by DOAC removal treatment. DOAC removal resulted in shortening of the dRVVT in 91% of the samples. Surprisingly, 6 cases showed prolongation in the dRVVT after DOAC removal. Before DOAC removal, 47 cases (24 apixaban and 23 rivaroxaban) tested positive and 17 tested negative (15 apixaban and 2 rivaroxaban). Following DOAC removal, 28 cases tested positive and 36 tested negative. As expected, many samples of patients on DOAC were found to be falsely positive (27/64; 15 on apixaban and 12 on rivaroxaban). Interestingly, 8 of 64 tests were found to be falsely negative. Of the 8 samples that were falsely negative, 7 were on apixaban and 1 on rivaroxaban. 9 samples that were negative before DOAC removal remained negative after DOAC removal, and 20 tests that were positive before DOAC removal remained positive after DOAC removal for a total of 29 results (45%) that remained unchanged. It was found that DOACs caused inaccurate results in 55% of cases. Conclusions: Our study was able to demonstrate the effectiveness of DOAC-Remove to eliminate DOACs from patient plasma and provide accurate LA results. DOAC interference on LA assays predictably creates many false positive results, however, presence of DOACs can produce false negative results as well, underlying the importance of pretest screening for presence of anticoagulants in plasma samples.